The Effect of Work Motivation as an Intervening Variable on Employee Performance - Nurdiniati, Gita; Entang, H. M.; Hannan, Sufrin (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
In order to realize national goals, the State Civil Apparatus (Aparatur Sipil Negara/ASN) is needed which is given the task of carrying out public service tasks, government tasks and certain development tasks. The purpose of the research is to find efforts to improve performance through identification of variables that are thought to affect performance. Based on the initial survey in terms of work quantity, namely there are still employees who have not completed the work according to the targeted amount, there are still employees who have not been able to do additional tasks given by superiors and employees. The results of the study that organizational climate is proven to have a positive direct effect on employee performance, organizational climate is proven to have a positive direct effect on work motivation. In this study, organizational climate variables affect work motivation, Interpersonal communication has a positive direct effect on and employee performance. Interpersonal communication has a positive direct effect on and work motivation. Work motivation has a positive direct effect on employee performance. Organizational climate has an indirect effect on employee performance through work motivation. Interpersonal communication has no indirect effect on employee performance through work motivation.